The Sins of Leo McCarey - Blake, Richard A. (The journal of religion and film, 2013)
Leo McCarey has received little attention from film scholars. His sentimentalizing his Catholic background and his preoccupation with anti-Communism obscured the lasting value of much of his work. His concern with sin and forgiveness form a major motif of his works, from the early comedies to his later serious dramas.